46 - ELF-IMAGE IN BODYBUILDING PRACTITIONERS (Fiep Bulletin - online, 2022)
Due to the increased concern with body image, something that is provided and accentuated by the media that end up propagating an overvaluation of aesthetic standards, the practice of physical activity comes to help people who, when self-evaluating, do not see themselves with good eyes, helping not only in body aesthetics, but also improving health in general. The objective of this work is to analyze the self-image in bodybuilders from the city of Patos PB. This is descriptive research and its design is cross-sectional. A sample of 50 bodybuilding students. The questionnaire used was the Body Image Questionnaire (Body Shape Questionnaire – BSQ). Descriptive analysis, based on mean, standard deviation, minimum and maximum value and absolute and relative frequency. The result of the research was that of the 50 people analyzed through the questionnaire 47 had no image distortion, 1 had moderate image distortion, 1 had mild image distortion and only 1 had severe image distortion. Conclusion that the study showed the importance of physical exercise and specifically weight training, showing effectiveness in the assessment of self-image.